2014
DOI: 10.1073/pnas.1400759111
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of mammalian kinesin-3 motors results in superprocessive motion

Abstract: The kinesin-3 family is one of the largest among the kinesin superfamily and its members play important roles in a wide range of cellular transport activities, yet the molecular mechanisms of kinesin-3 regulation and cargo transport are largely unknown. We performed a comprehensive analysis of mammalian kinesin-3 motors from three different subfamilies (KIF1, KIF13, and KIF16). Using Forster resonance energy transfer microscopy in live cells, we show for the first time to our knowledge that KIF16B motors under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
288
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 186 publications
(325 citation statements)
references
References 59 publications
36
288
1
Order By: Relevance
“…In contrast, KIF16B is a monomer in the cytoplasm and dimerizes at the cargo surface. The localized dimerization of KIF16B on early endosomes has been directly observed using Fцrster resonance energy transfer (FRET) in live cells [58]. Thus, these examples support the idea that due to the diverse cargo binding tail, the different kinesin 3 fam ily members use diverse means of autoinhibition and cargo dependent release of inhibition, involving changes in the dimerization status for some members and compet itive binding of a peptide region that weakly interacts with the motor domain for others.…”
Section: Activation By Cargo Interactionmentioning
confidence: 59%
See 3 more Smart Citations
“…In contrast, KIF16B is a monomer in the cytoplasm and dimerizes at the cargo surface. The localized dimerization of KIF16B on early endosomes has been directly observed using Fцrster resonance energy transfer (FRET) in live cells [58]. Thus, these examples support the idea that due to the diverse cargo binding tail, the different kinesin 3 fam ily members use diverse means of autoinhibition and cargo dependent release of inhibition, involving changes in the dimerization status for some members and compet itive binding of a peptide region that weakly interacts with the motor domain for others.…”
Section: Activation By Cargo Interactionmentioning
confidence: 59%
“…In KIF1A, KIF13A, and KIF13B, the coiled coil domains seem to interfere with dimerization. It has been shown that instead, the neck coil alone efficiently dimerizes these motors [57,58].…”
Section: Structure Of Kinesin 3 Motorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another shared feature of transport kinesins is their ability to move processively (i.e. take many steps upon binding to a microtubule), which enables efficient long-distance transport by single motors (Howard et al, 1989;Soppina et al, 2014;Yamazaki et al, 1995). Consistent with a transport function, dimeric FRA1 motors have been found to move processively both in vitro and in vivo (Kong et al, 2015;Zhu and Dixit, 2011;Zhu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%